Establishment of somatic embryogenesis from Gerbera jamesonii Bolus EX. Hook F. through suspension culture - Hasbullah, N.A.; Saleh, A.; Taha, Rosna Mat (Academic Journals, 2011)
Cell suspension cultures were established from embryogenic callus induced from leaf explants of Gerbera jamesonii Bolus ex. Hook f. Embryogenic callus was induced when leaf explants were cultured on MS medium containing 1.0 to 2.0 mg/L 2,4-D. Cream friable callus was formed within two weeks. Proliferated callus was transferred to MS liquid medium containing 2,4-D with a small concentration of NAA and subcultured at 2 weeks interval. Induction of somatic embryos (globular, heart and torpedo) was observed after 2 weeks of culture. Somatic embryos developed in MS suspension medium containing 1.0 to 2.0 mg/L 2,4-D with 0.1 or 1.0 mg/L NAA and globular embryos were further differentiated into the cotyledonary phase embryos. The addition of amino acids (L-glutamine or L-proline, 5.0 mg/L, respectively) to the culture media, in the range of concentrations tested, yielded higher enhancement of the embryo growth and development. Transfer of individual embryos onto a fresh basal medium with no plant growth regulators was able to achieve complete maturation. Relatively, only a few number of embryos developed shoots and roots when transferred to MS medium supplemented with 2.0 mg/L BAP and 0.5 mg/L NAA in addition to 3 (w/v) sucrose and 0.8 (w/v) agar containing medium. About 11 of somatic embryos were converted to true-to-type fertile plants.